Exploitation of the full potential of Persistent Scatterer Interferometry data - M. Crosetto; N. Devanthéry; M. Cuevas-González; O. Monserrat; B. Crippa (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2014)
The potential of Persistent Scatterer Interferometry (PSI) for deformation monitoring has been increasing in the last years and it will continue to do so in the short future, especially with the advent of the Sentinel-1 mission. The full exploitation of this potential requires two important components. The first one is the improvement of the PSI processing tools, to achieve massive and systematic data processing capabilities. The second one is the need to increase the capabilities to correctly analyze and interpret the PSI results. The paper addresses both components. The key features of the PSI processing chain implemented by the authors, which is named PSIG chain, are described. This is followed by a brief discussion of the key elements needed to analyse and interpret the results of a given PSI processing. The paper concludes with a description of the results obtained by processing a full frame of very high resolution TerraSAR-X data that covers the metropolitan area of Barcelona (Spain).